Transformation of English Language Teaching in Elementary Schools: Analysis of Teacher Pedagogical Competence through TPACK - Farikah (LETS: Journal of Linguistics and English Teaching Studies, 2026)
The digital transformation of English Language Teaching (ELT) requires elementary teachers to integrate technology with sound pedagogy rather than to add it as a surface-level enhancement. Yet little is known about how non-specialist teachers of young learners enact such integration, and conventional evaluations tend to assess technological and pedagogical competence in isolation. This exploratory study investigates the perceived and enacted pedagogical competence of elementary English teachers through the Technological Pedagogical Content Knowledge (TPACK) framework and a multimodal lens. A convergent mixed-methods design was applied, in which a descriptive quantitative strand (a self-report questionnaire) and a qualitative strand (interviews and structured observation) were collected concurrently and then merged for interpretation, with 55 elementary English teachers in Magelang Regency, Indonesia, selected through purposive sampling across three career stages. Data were collected through a 12-indicator self-report questionnaire (five-point Likert scale), semi-structured interviews with 15 teachers, and structured observations of 18 lessons coded against a TPACK-multimodal rubric; the quantitative and qualitative strands were merged through a joint display. Self-report means were uniformly high (4.0-4.4), with the lowest scores in the integrative dimensions Technological Pedagogical Knowledge (TPK) and Technological Content Knowledge (TCK, both 4.0). Observation evidence, however, diverged from these perceptions: in most lessons technology functioned as substitution (displaying static text or playing audio) rather than transformation, and only about one fifth of observed lessons showed simultaneous integration of technology, pedagogy, and language content. Multimodal practice was dominated by the visual mode, with audio and gestural modes used less and assessed inconsistently. The study contributes an evidence-based mapping of the gap between perceived and enacted TPACK in primary ELT and offers proportionate implications for sustained, practice-based teacher professional development. Because the findings rest on self-report and a bounded sample, they are interpreted as indicative rather than conclusive, and no claims are made about student learning outcomes.